Psychological And Pedagogical Patterns of The Process of Comprehension and Comprehension of Educational Material by Students - Shakhmuradova Dilzhakhon Almardonovna (Genius Publishing Group, 2024)
The article has a psychological and pedagogical character of the process of comprehension and understanding of educational material by students and tells about the processes of cognition and understanding of educational material by students.
Keywords: learning; knowledge; activity